1973
DOI: 10.1111/j.1748-5827.1973.tb06408.x
|View full text |Cite
|
Sign up to set email alerts
|

The long term results of surgery of canine stifle disorders

Abstract: The case histories, treatment and post–operative progress of 297 dogs referred to this Department for investigation of stifle conditions between September 1968 and September 1972 are described with particular emphasis on the long term results of treatment. Résumé. Les antécédents commémoratifs, le traitement et les progrès postopératoires de 297 chiens, remis à ce département entre Septembre 1968 et Septembre 1972 pour investigation à l'égard de l'état du grasset, ont été décrits en mettant surtout l'emphase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
27
2

Year Published

1985
1985
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 10 publications
13
27
2
Order By: Relevance
“…The smaller reported number came from a study 20 in which investigators only counted patellar reluxation if it required surgical intervention. 6,14,18 The described minor complication rate of 34.1% of cases in the present study is slightly higher than those reported in other studies [18][19][20] (reports ranged from 23/131 [17.6%] stifle joints to 20/70 [28.6%] dogs). The proportion of cases in which additional surgery was recommended for patellar reluxation or other major complications in the present study (6/91 [6.6%]) also compares favorably with those of previous reports 19,20 (8/70 [11.4%] dogs to 17/131 [13.0%] stifle joints).…”
Section: Discussioncontrasting
confidence: 66%
See 3 more Smart Citations
“…The smaller reported number came from a study 20 in which investigators only counted patellar reluxation if it required surgical intervention. 6,14,18 The described minor complication rate of 34.1% of cases in the present study is slightly higher than those reported in other studies [18][19][20] (reports ranged from 23/131 [17.6%] stifle joints to 20/70 [28.6%] dogs). The proportion of cases in which additional surgery was recommended for patellar reluxation or other major complications in the present study (6/91 [6.6%]) also compares favorably with those of previous reports 19,20 (8/70 [11.4%] dogs to 17/131 [13.0%] stifle joints).…”
Section: Discussioncontrasting
confidence: 66%
“…Our hypothesis was that luxation recurrence and complication rates following this surgical procedure would be similar to those reported in studies 1,3,6,14,15,[18][19][20]22,23 in which the surgical techniques included trochlear groove deepening procedures. We sought to assess signalment, outcomes, and associated complications for dogs that received this treatment and to evaluate whether OA progressed during the 8-week period following surgery.…”
supporting
confidence: 59%
See 2 more Smart Citations
“…A number of papers proved a higher incidence of the CCL rupture in females than in males (Barnes 1977;Denny and Minter 1973;Whitehair et al 1993). In our sample of patients males and females were rather equally represented (53.55% of males and 46.45% of females).…”
Section: Discussionmentioning
confidence: 99%